Generation of a genetically modified pig model with CREBRFR457Q variant. Issue 11 (17th October 2022) - Li, Yingying; Wang, Hai; Chen, Huangyao; Liao, Yuan; Gou, Shixue; Yan, Quanmei; Zhuang, Zhenpeng; Li, Hao; Wang, Jiaowei; Suo, Yangyang; Lan, Ting; Liu, Yang; et al.
Abstract: Obesity is among the strongest risk factors for type 2 diabetes (T2D). The CREBRF missense allele rs373863828 (p. Arg457Gln, p. R457Q) is associated with increased body mass index but reduced risk of T2D in people of Pacific ancestry. To investigate the functional consequences of the CREBRF variant, we introduced the corresponding human mutation R457Q into the porcine genome. The CREBRF R457Q pigs displayed dramatically increased fat deposition, which was mainly distributed in subcutaneous adipose tissue other than visceral adipose tissue. The CREBRF R457Q variant promoted preadipocyte differentiation. The increased differentiation capacity of precursor adipocytes conferred pigs the unique histological phenotype that adipocytes had a smaller size but a greater number in subcutaneous adipose tissue (SAT) of CREBRF R457Q variant pigs. In addition, in SAT of CREBRF R457Q pigs, the contents of the peroxidative metabolites 4‐hydroxy‐nonenal and malondialdehyde were significantly decreased, while the activity of antioxidant enzymes, such as glutathione peroxidase, superoxide dismutase, and catalase, was increased, which was in accordance with the declined level of the reactive oxygen species (ROS) in CREBRF R457Q pigs. Together, these data supported a causal role of the CREBRF R457Q variant in the pathogenesis of obesity, partly via adipocyte hyperplasia, and further suggested that reduced oxidative stress in adipose tissue may mediate the relative metabolic protection afforded by this variant despite the related obesity.